DRIVERS BEHIND JAPAN’S DEFENSE BUDGET SURGE(2013-2023): THREAT PERCEPTIONS AND POLITICAL SUPPORT - Ardra Galih Asasta; Febry Triantama (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2025)
Japan since 2013 has increased its defense budget significantly and consistently annually. Recently in 2022 a decision was approved to increase the defense budget to the target of 2% of its GDP in 2027. Empirically from 2013 it amounted to ¥4.6 trillion which increased slowly until 2022 with the target starting to increase significantly to ¥8.7 trillion in 2025. The move was motivated by the perceived threat of China, North Korea, and Russia surpassing Japan's defense. This study analyzes the significant and consistent increase in defense budget from 2013 to 2023. The data was analyzed using the determinants that influence the allocation of the national defense budget by Triantama and Abdul (2023) with qualitative research methods. The results show that there is a high threat perception, strong military ambition, and civilian support that encourages Japan to continue to increase its defense budget until it reaches the target in 2027.